Tabuh Lelambatan Klakat Sudhamala: A New Creative Musical Composition | Tabuh Lelambatan Klakat Sudhamala: Sebuah Komposisi Karawitan Kreasi Baru - I Gede Janu Merta Yasa; Ni Putu Tisna Andayani (GHURNITA: Jurnal Seni Karawitan, 2021)
The process of creating works of art, especially musical art, has begun to develop following the times. The development is in the process of creativity in the creation of musical art, it can be seen from the musical elements in musical art. In musical art it is very important in the process of creating a strong work of art for a renewal of tradition so that it can be said as creative music. The composer is interested to appoint the klakat sudamala which is woven bamboo as a braid of the composition of the drum percussion which is woven bamboo as an interwoven composition of the percussion of tabuh lelambatan collaborated in the gamelan Gong Kebyar as a medium of expression by using the two percussion pattern as the structure of the composition.The composer certainly has intends to achieve his goal, so that his work has a meaning to be used as the accompaniment of instruments (tabuh) when holding a yadnya ceremony in his village. The creative process of creating the composition tabuh dua "Klakat Sudamala" is inseparable from the process of creating works of art by Alma M Hawkins. Hopefully, the creation of the tabuh lelambatan contributes to the village in particular and to the Balinese musical world in general.